Evaluating the mechanical and environmental impact of PEF plastic waste incorporated with graphene nano-platelets in concrete - Khan, Muhammad Basit; Najeh, Taoufik; Almujibah, Hamad; Al Zouabi, Mohammad Ghiath; Benjeddou, Omrane (Frontiers in Materials, 2024)
There has been a significant surge in the yearly use of plastics, leading to a notable rise in plastic waste generation. Consequently, the recycling of plastic garbage has emerged as a prominent concern around the world. This research explores the feasibility of using polyethylene furanoate (PEF) plastic waste as a substitute for coarse aggregate (CA) in concrete. Graphene nano-platelets (GNPs) were added to the concrete mix in different quantities to improve its structural reliability. The research study used an experimental research design in conducting its investigation. PEF waste plastic was added in concrete in varying proportions of 0%, 5%, 15%, 20%, and 25% as a supplementary material to gravel, and GNPs were added in different percentages of 0%, 0.03%, 0.05%, 0.08%, and 0.1% by weight of cement. Mechanical tests were conducted, which includes compressive strength (CS), split tensile strength (STS), flexural strength (FS), modulus of elasticity (MoE), and ultrasonic pulse velocity (UPV), and the environmental assessment of concrete was done by assessing carbon in concrete and concrete’s eco efficiency (ESE). It was found that 5% addition of PEF as the substitute to CA and 0.1% of GNPs gives the optimum strength, enhancing CS, STS, and FS by 9.10%, 18.18%, and 4.45%, respectively. Response surface technique (RSM) models were created to provide mathematical equations for predicting the predicted outcomes. All models were optimized using a multi-objective optimization approach and then validated.